2019
DOI: 10.3168/jds.2018-14981
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of gestation length and its use in managing calving patterns

Abstract: Data collected from Australian Holstein cows that calved between 1995 and 2016 were used for estimating genetic parameters and genetic evaluation of gestation length (GL). Genetic parameters were estimated using a sire maternal grandsire model considering GL in heifers as correlated, but a different trait to adult cows and animal repeatability model. The key objective of this study was to assess if selective mating of bulls with short GL estimated breeding values (EBV) can help to modify calving patterns in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
4
9
0
Order By: Relevance
“…The data used in the present study was provided by DataGene Pty Ltd (Melbourne, Australia). In Australia, the dominant dairy farming system is a pasture-based seasonal production system with a low level of supplementation (Haile-Mariam and Pryce 2019;Ooi et al 2021). The data consisted of survival TDs for 538 394 pure Holstein and 63 839 pure Jersey cows.…”
Section: Datamentioning
confidence: 99%
“…The data used in the present study was provided by DataGene Pty Ltd (Melbourne, Australia). In Australia, the dominant dairy farming system is a pasture-based seasonal production system with a low level of supplementation (Haile-Mariam and Pryce 2019;Ooi et al 2021). The data consisted of survival TDs for 538 394 pure Holstein and 63 839 pure Jersey cows.…”
Section: Datamentioning
confidence: 99%
“…The data were also checked for unusual milk fat and protein contents (i.e., 1.5 g/dL of milk < fat < 9 g/dL of milk, 1 g/dL of milk < protein < 7 g/dL of milk) and SCC (0.01% upper values were deleted) following the recommendation of the International Committee for Animal Recording (ICAR, 2017b). Finally, gestation length was restricted to be from 250 to 300 d, because the average for Australian Holsteins is 281 d (Haile-Mariam and Pryce, 2019).…”
Section: Data Preprocessingmentioning
confidence: 99%
“…There are a number of factors identified to impact GL such as genetics, month of conception (or calving), age and parity of the dam, calf gender, litter size (single vs. double), the number of days in milk, and the level of milk production (Silva et al, 1992;Nogalski and Piwczyński, 2012;Tomasek et al, 2017). Although the GL is not included in genetic evaluations in most countries, several studies have confirmed that genetic variation for GL is large enough to change it through selection (Chud et al, 2014;Silveira et al, 2015;Lacerda et al, 2018;Haile-Mariam and Pryce, 2019). The GL is associated with a number of economically important traits, including lactation performance, productive life, health traits, calving ease and calf mortality (Hansen et al, 2004;Vieira-Neto et al, 2017;Haile-Mariam and Pryce, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the GL is not included in genetic evaluations in most countries, several studies have confirmed that genetic variation for GL is large enough to change it through selection (Chud et al, 2014;Silveira et al, 2015;Lacerda et al, 2018;Haile-Mariam and Pryce, 2019). The GL is associated with a number of economically important traits, including lactation performance, productive life, health traits, calving ease and calf mortality (Hansen et al, 2004;Vieira-Neto et al, 2017;Haile-Mariam and Pryce, 2019). It has shown that longer GL is associated with higher calf birth weight and a higher rate of dystocia which can result in a higher rate of calf and cow mortality and longer postpartum interval (Meijering 1984;Hansen et al, 2004;Chud et al, 2014;Jamrozik and Miller, 2014).…”
Section: Introductionmentioning
confidence: 99%